التماثل التنظيمي - مصباحي, حكيمة; بوبيدي, لمياء (جامعة الوادي - University of Eloued, 2023)
ملخص: يعد موضوع التماثل التنظيمي من الموضوعات التي أثارت اهتمام العلماء في مجال علوم الإدارة وعلم النفس وعلم الاجتماع ..... , لما له من أهمية بالغة في تحقيق أهداف المنظمة. إن تحقيق التماثل التنظيمي يتحدد من خلال تلك التشابهات في القيم و السلوك و الأهداف لدى العاملين .والتي بدورها تتماثل مع بنية المنظمة وهويتها جاعلة من العاملين باعتبارهم فعالين والمنظمة كيانا حيويا منسجما بنيويا ومتكاملا وظيفيا . جاء هذا المقال كقراءة سوسيو مفاهمية للتماثل التنظيمي ,من خلال تسليط الضوء على محدداته ونظرياته التحليلية المختلفة الكلاسيكية منها والحديثة . Abstract: The subject of organizational symmetry is one of the topics that aroused the interest of scholars in the field of management sciences, psychology and sociology ..... , because of its great importance in achieving the goals of the organization. The achievement of organizational symmetry is determined through those similarities in the values, behavior and goals of the workers. Which in turn corresponds to the structure and identity of the organization, making the workers as effective and the organization as a vital entity, structurally consistent and functionally integrated. This article came as a socio-conceptual reading of organizational symmetry, by shedding light on its determinants and various analytical theories, both classical and modern.
قراءة سوسيو مفاهيمية
مقال
Keywords: قراءة مفاهيمية ; تماثل تنظيمي; A Socio-Conceptual Reading; organizational symmetry